The involvement of coordinative interactions in the binding of dihydrolipoamide dehydrogenase to titanium dioxide—Localization of a putative binding site. Issue 8 (28th February 2017) - Dayan, Avraham; Babin, Gilad; Ganoth, Assaf; Kayouf, Nivin Samir; Nitoker Eliaz, Neta; Mukkala, Srijana; Tsfadia, Yossi; Fleminger, Gideon
Abstract: Titanium (Ti) and its alloys are widely used in orthodontic and orthopedic implants by virtue to their high biocompatibility, mechanical strength, and high resistance to corrosion. Biointegration of the implants with the tissue requires strong interactions, which involve biological molecules, proteins in particular, with metal oxide surfaces. An exocellular high‐affinity titanium dioxide (TiO2 )–binding protein (TiBP), purified from Rhodococcus ruber, has been previously studied in our lab. This protein was shown to be homologous with the orthologous cytoplasmic rhodococcal dihydrolipoamide dehydrogenase (rhDLDH). We have found that rhDLDH and its human homolog (hDLDH) share the TiO2 ‐binding capabilities with TiBP. Intrigued by the unique TiO2 ‐binding properties of hDLDH, we anticipated that it may serve as a molecular bridge between Ti‐based medical structures and human tissues. The objective of the current study was to locate the region and the amino acids of the protein that mediate the protein‐TiO2 surface interaction. We demonstrated the role of acidic amino acids in the nonelectrostatic enzyme/dioxide interactions at neutral pH. The observation that the interaction of DLDH with various metal oxides is independent of their isoelectric values strengthens this notion. DLDH does not lose its enzymatic activity upon binding to TiO2, indicating that neither the enzyme undergoes major conformational changes nor the TiO2 binding site is blocked. Docking predictions suggest that both rhDLDH and hDLDH bind TiO2 through similar regions located far from the active site and the dimerization sites. The putative TiO2 ‐binding regions of both the bacterial and human enzymes were found to contain a CHED (Cys, His, Glu, Asp) motif, which has been shown to participate in metal‐binding sites in proteins. Abstract : Strong interactions between dihydrolipoamide dehydrogenase (DLDH) and titanium dioxide (TiO2 ) are exemplified. By a series of biochemical and biophysical methods these interactions are shown to be nonelectrostatic, presumably of coordinative nature. Docking predictions suggest a putative binding site of the protein to the TiO2 surface.